Effect of process parameters to flexural strength of 3D printed anatomical bone part - T. Tajarernmuang (2020)
© Published under licence by IOP Publishing Ltd. Training and practice on synthetic anatomical bone before perform real medical operation is useful for medical student and recently become part of medical procedure. Since there are various factors to considered, the attempt to imitate anatomical bone from medical image data of patient, using technology that based on Fused Deposition Modelling (FDM) is alternatively developed. Since durability and qualities of 3D printed model depend on process parameters which referred to 3D printer setting, this study aims to investigate effect of essential 3D printer setting parameters involve with mechanical properties of 3D printed anatomical bone part, focused on infill density and layer height, and determine regression model for mechanical strength prediction from selected printing parameters by using experimental design and statistical analysis that based on Design of Experiments (DOE). 2-levelled full factorial experiment was designed, 3 factors including layer height, infill density, and print speed were taken into account. After that, selected 27 Mid-section of femur bone from 3D medical image data were fabricated from filament of Poly-lactic acid (PLA). The models were underwent a three-point bending testing to investigate mechanical properties and statistical analyse to investigate the relationship of parameters.